Environmental and geographical factors influence malaria transmission in KwaZulu-Natal province, South Africa - Osadolor Ebhuoma; Michael Gebreslasie; Oswaldo Villena; Ali Arab (Geospatial Health)
The malaria burden remains largely concentrated in sub- Saharan Africa. South Africa, a country within this region, has made significant progress toward malaria elimination. However, malaria continues to be endemic in three of its nine provinces: Limpopo, Mpumalanga, and KwaZulu-Natal (KZN), which are located in the northern part of the country and share borders with Botswana, Zimbabwe, and Mozambique. This study focuses on KZN, where district municipalities report monthly malaria cases ranging from zero to 8,981. Fitting Bayesian zero-inflated models in the INLA R package, we assessed the effects of various climate and environmental variables on malaria prevalence and spatio-temporal transmission dynamics from 2005-2014. Specifically, we analyzed precipitation, day and night land surface temperature, the Normalized Difference Vegetation Index (NDVI), the Enhanced Vegetation Index (EVI) and elevation data for KZN local municipalities. Our findings indicate that the best model was the Zero- Inflated Negative Binomial (ZINB) and that at 95% Bayesian Credible Interval (CI), NDVI (0.74; CI (0.95, 3.87) is significantly related to malaria transmission in KZN, with the north-eastern part of the province exhibiting the highest risk of malaria transmission. Additionally, our model captured the reduction of malaria from 2005 to 2010 and the following resurgence. The modelling approach employed in this study represents a valuable tool for understanding and monitoring the influence of climate and environmental variables on the spatial heterogeneity of malaria. Also, this study reveals the need to strengthen the already existing crossborder collaborations to fortify KZN’s malaria elimination goals.